Positive mental activity
This fourth issue of Coaching Science Abstracts reviews articles concerned with positive mental activity. It is not possible to talk on this general topic under one separate heading. This issue has been divided into five sections. A. Basic Research is concerned with research articles not involving sport or physical activity but which have important principles and action guidelines that might be useful if applied or researched in sport settings. B. Self-talk relates sport-specific research that assesses the effects and dynamics of athlete self-talk on performance. This topic suggests that coaches must pay attention to the type of mental dialogue in which athletes engage. C. Coach's Influence reports on a number of studies which relate coaching behaviors to the covert dialogue of athletes. These show that a coach can affect the self-talk of athletes in an unintentional way purely by their behaviors and speech content. D. Positive Thinking covers a variety of topics which embrace general categories of positive thinking. It is assumed that self-talk underlies most of the concepts considered but their interaction with sporting experiences will affect consequent behaviors. Each abstract should be considered and its implications for specific coaching behaviors noted and, hopefully, implemented. E. Suggested Reading provides a reference for a sport-specific self-help manual that is designed to alter many of the skills and activities discussed in this issue. It is possible for coaches to require athletes to perform mental skills training exercises without an unreasonable investment of the coach's time. The main impact of this issue should be the realization that positive mental activities, interpretations of sporting experiences, and the nature of external events can affect performance in a beneficial manner. Sources of negative impact have largely been ignored. Attention to the factors discussed in the following abstracts is an avenue for generating performance improvements. You can read the articles seperately from the main page on.